Parenting Patterns and Its Implications for Formation Religious Character in Early Childhood (KONSELING RELIGI, 2020)
The purpose of this study was to determine which form of parenting is the most dominant applied by parents in instilling religious characters in early childhood. Parenting is a process in the family, the interaction between parents and children. Parenting patterns have been applied since the child was born and adjusted to the age and stage of development. Learning in early childhood is the initial foundation of character building in children. Religious character education should be carried out comprehensively, covering all aspects of education, from the preparation of children from birth to efforts to strengthen children's physical and spiritual abilities, conveyed with advice, with examples well as well as with the process of getting used to good things so that it has implications for the personality of the child in adulthood. This study used an analysis descriptive qualitative method. To collect data, the researcher used three methods, namely: interview method, documentation, and observation method. The results showed that the parenting style of parents and its implications for the formation of a religious character in early childhood at TK Al-Hikmah Karangbesuki Sukun Malang is democratic and permissive parenting which is the most dominant applied.